1974
DOI: 10.3758/bf03213954
|View full text |Cite
|
Sign up to set email alerts
|

A tactile illusion: The rotating hourglass

Abstract: A new tactile (more properly termed haptic) illusion, the rotating hourglass, was investigated in the laboratory by rotating a rod end for end between the S's thumb and forefinger. This illusion, which is an apparent decrease in the diameter of the rod at the point of contact with the fingers, was easily observed by 19 of the 20 Ss. When the illusion was studied as a function of time, the magnitude of the illusion increased over time with a mean decrease in apparent diameter of 52.3% from the beginning to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Every sensory modality seems to exhibit such adaptation: vision (Hurley 2002), audition (Jerger 1957;Ylikoski & Lehtosalo 1985), touch (Jones, Gettys, & Touchstone 1974), and olfaction (Dalton 2000). But the most important reason to consider neural adaptation as the underpinning of anapoiesis is the fact that adaptation does not result from fatigue of neurons (as has been often incorrectly presumed) but that neural adaptation rather reflects a certain form of cybernetic knowledge-i.e., the neuron has made a "decision" not to fire.…”
Section: Prediction 1: Cognitive Operations Are Implemented Chiefly Tmentioning
confidence: 99%
“…Every sensory modality seems to exhibit such adaptation: vision (Hurley 2002), audition (Jerger 1957;Ylikoski & Lehtosalo 1985), touch (Jones, Gettys, & Touchstone 1974), and olfaction (Dalton 2000). But the most important reason to consider neural adaptation as the underpinning of anapoiesis is the fact that adaptation does not result from fatigue of neurons (as has been often incorrectly presumed) but that neural adaptation rather reflects a certain form of cybernetic knowledge-i.e., the neuron has made a "decision" not to fire.…”
Section: Prediction 1: Cognitive Operations Are Implemented Chiefly Tmentioning
confidence: 99%
“…The only example of another instance in which the perceived distance between the fingers is influenced by tactile input are the rotating disk and rotating hourglass illusions [2,6]. When a coin is rotated between thumb and index finger, the coin is perceived to be elongated perpendicular to the rotation axis, while the coin in the direction of the rotation axis sometimes is reported to shrink [2].…”
Section: Resultsmentioning
confidence: 97%
“…A similar effect is known as the rotating hourglass illusion. A rod rotated between thumb and index finger is perceived to be hourglass shaped [6]. The authors that found the hourglass illusion suggested that both illusions are caused by a pressure differential on the skin of the finger pad.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A differential adaptation theory was proposed previously to explain two haptic illusions (Jones, Touchstone, & Gettys, 1974). In the present paper, this theory was used to produce two new illusions.…”
mentioning
confidence: 94%